The Relationship Between Job Satisfaction and Organizational Commitment in Female Employees - Pehlivanoğlu, M.Çağrı; Eymür, Emre; Civelek, Mustafa Emre (Journal of Applied And Theoretical Social Sciences, 2022)
In this study the relationship between job satisfaction and organizational commitment in female employees has been examined. The structural equation modelling technique was used to analyze complex models with both direct and indirect relationships. Quantitative data was gathered by utilizing questionnaires. To demonstrate convergence validity, confirmatory factor analysis was used. Composite reliability and AVE scores were calculated to assess the scales' reliability and discriminant validity. The AMOS statistical program's structural equation model method was used to test the hypotheses. Out of six hypotheses, two of them were supported. It has been empirically proven that Internal Job Satisfaction has a direct effect on Affective Commitment and Normative Commitment, where External Job Satisfaction does not have a direct effect on any sub-dimensions of organizational commitment. Although job satisfaction and organizational commitment have been examined individually in many studies, this research focused on female employees working in the service sector while evaluating the relationship between the two concepts in the light of current data.